Shari’ah-complaint Hotel: operational scenarios, Shari’ah parameters and opportunities for the contemporary hospitality industry - Adam Sa'ad, Auwal; Bashir Aliyu, Umar; Salina, Kassim; Sidi, Contey (2021)
Tourism, as an industry, is among the world’s largest and most-rapidly growing economic sectors (Mowforth, & Munt, 2015). The provision of hospitality and related services in line with Shari’ah principles, is otherwise referred to as “shariah-compliant hotel Saad et al. (2014), noted that, according to the statistics reported by the WTO in 2010, a sharäh-complaint -complaint hotel represents 10 % of the global tourism market. The total expenditure of Muslim tourists is estimated to be USD192 billion, which represents 13.36% of global tourism expenditure up to 2020, and the top destinations for Muslim tourists are Malaysia, Turkey, and the United Arab Emirates, followed by Singapore, Russia, China, France, Thailand, and Italy. The global halal industry is estimated to be worth USD 2.30 trillion (ibid). Furthermore, Muslims account for 29% of the global population, which means there are about 2 billion potential customers that would be attracted to enjoy and benefit from Shari’ah-compliant hotels (Saifuddin et al 2015).